Morphological characterization of gram-positive and gram-negative bacteria from treated latex processing wastewater - Dahalan, Farrah Aini; Azizah Parmin, Nor (Universitas Nahdlatul Ulama Surabaya, 2021)
A preliminary morphological screening and isolation of bacterial colony from latex industrial wastewater was carried out. Bacteria colonies from latex processing wastewater were isolated from a local latex processing industry. It was found that 17 bacterial isolates had been purified grown on nutrient agar under 35˚C. The colonies were then purified and morphologically indicated via Gram staining and motility test. After morphological observation, it was identified that out of 17 isolates, 9 isolates were Gram positive and 8 isolates were Gram negative. There are 11 out of 17 colonies were rod-shaped bacterial colonies, while the other 6 colonies were cocci-shaped bacteria. There were 11 colonies of gliding bacteria, three colonies were non-motile bacteria and the other three colonies were flagellated bacteria. This study is only limited to morphological observation as the main aim of this study was to investigate the potential occurrence of viable growth in treated latex processing wastewater. The bacterial colonies were classified base on their morphological properties shown. This study has classified several genera such as Staphylococcus, Escherichia, Thiobacillus, Arthrobacter and other Genus. The growth curve of 17 isolates studied and the chemical oxygen demand were determined.